Uncertainty of building regulation for refurbishment projects in Malaysia - Ali, A.S.; Che-Ani, A.I.; Wan Yusoff, W.Z. (2010)
The uncertainty of refurbishment projects is reflected in the difficulty in getting accurate design information during the design process. One of the factors contributing to the uncertainty in refurbishment projects is building legislation. The changing and updating some of the building regulations by government has also affected the approval process in refurbishment projects, especially projects related to conservation. The statutory requirements could cause project delays and cost overruns due to adjustments that need to be made to design in order to comply with the regulations. Therefore, the main objectives of this paper are to present the difficulties that contributed to the uncertainty of building legislation and to show how it affects the overall performance of refurbishment projects. Quantitative research techniques are used, which consists of review of literature and a postal questionnaire survey that involved 234 respondents. From 234 questionnaires sent out, 62 questionnaires were found to be suitable to form a database for analysis. Descriptive and inferential statistics are used in the data analysis. The results conclude that complexity in refurbishment projects in Malaysia is made worse by uncertainty of building legislation. The associative test indicates that performance of refurbishment projects suffered from the uncertainty of building regulations.